Unconventional History: Sixty Years of Science and Technology in Hydraulic Fracturing - Minisini, Daniel (2017)
More than ten years have passed since the energy revolution driven by the production of the so called Unconventional Plays. In this short time span, Industry has moved from a general secretive and confidential treatment of data to a more relaxed method of data sharing that has allowed cooperation in an environment of competition. We call this form of scientific communication ?co-opetition?. Our co-opetition arose from the Vaca Muerta Unconventinal Play (Argentina), one the best producers in the world and it represents an important shift in the data sharing of technical information in the Oil & Gas Industry. The small profit margins typical of the unconventional business dictated the need to rapidly characterize the subsurface rocks in order to be predictive. Hence, the nature of the business in this new technological frontier of unconventional plays forced the scientific community to create a new model for communication and data sharing. Our co-opetition optimizes the expensive data collected by each company by sharing it and putting it in a broader context that is built and vetted by all the other players, in a ?check and balance? fashion. Once the data and the agreed context are in place, then each player differentiates by their own interpretations.